Fournier’s Gangrene in Woman after Indonesian Traditional Therapy: A Case Report - Aulia, Riean; Dahril, Dahril (Journal of Neonatal Surgery, 2025)
Introduction: Fournier’s gangrene (FG) is an extremely rare form of necrotizing fasciitis which is a very rapidly progressive disease that attacks deep and superficial tissues in the perineum, anus, scrotum, and genital areas. The incidence is reported to be very rare, around 1.6 to 3 per 100,000 with a ratio between men and women of 10:1. Early diagnosis and early treatment of this disease is the main key to preventing worsening. We report a unique case, namely a woman with Fournier's gangrene who previously received alternative therapy with hot bricks. Case Presentation: A 61-year-old woman was referred from a secondary hospital with a diagnosis of fasciitis necroticans. Based on the history of the disease obtained from the anamnesis, the patient initially complained that there was a lump in the anal region which was not known exactly when it first appeared. the patient took the initiative to carry out alternative treatment using hot bricks placed on the patient's buttocks. The patient was not routinely checked and was only treated at home for 4 months. The patient was diagnozed with Fournier’s gangrene based on clinical findings. Conclusion: Surgical emergency debridement therapy is a goal treatment of FG to prevent worsening of FG and septic shock